The Primacy of Accessibility in Urban Riverfront Tourism: An Empirical Integration of the 3A-TPB Framework in Banjarmasin, Indonesia - Arafat Alhally; Sahara Maghfiroh; Padli (Politeknik Negeri Bandung, 2026)
Urban riverfronts represent strategic recreational assets where terrestrial and aquatic mobility systems converge. Despite their economic significance, the psychological mechanisms governing visit decisions in high-density land-water interfaces remain insufficiently understood. This study examines the impact of attractions, amenities, and accessibility on visitor decisions at Siring Piere Tendean, Banjarmasin, using an integrated 3A-Theory of Planned Behavior (TPB) framework. Utilizing a quantitative survey (n=100) analyzed via multiple linear regression, the findings demonstrate that 3A attributes account for 52.6% of the variance in visit decisions. Notably, accessibility emerges as the dominant predictor, surpassing the influence of amenities and attractions. The data reveal that for the 83% of respondents who are repeat visitors, the riverfront operates as a functional utility hub where behavioral execution is dictated by the absence of mobility friction. Theoretically, this research anchors Perceived Behavioral Control in physical accessibility, establishing a